Use of ultrasound as a diagnostic method and therapeutic tool in dental practice. A review. - Pulgarín-Bedoya, Liliana María (2020)
In medicine, ultrasound is especially useful to evaluate intrauterine development, cyst behavior, and internal organs, but the use of ultrasound in dentistry has only recently been explored and used in the daily routine diagnostic methods in clinical dental practice. The growing interest in the useof ultrasound as a diagnostic and therapeutic method in dentistry has led to studies investigating its benefits in relation to accessibility, cost and innocuousness to health. This review describes the current use of ultrasound in different dental specialties and compares it with other diagnosticmethods.